Ruptured internal iliac artery aneurysm presenting with massive lower gastro intestinal haemorrhage - Thakur, Mohim; Vats, Ravinder; Goel, Deep; Bhalla, V. P. (International Surgery Journal, 2016)
A patient presenting with massive Lower Gastro Intestinal Haemorrhage (LGIH) in the tropics is most likely to be a young individual commonly bleeding from nonspecific or enteric ulcers. In contrast the western patient with massive LGIH is likely to be an elderly individual bleeding from diverticulosis or angiodysplasia. Recently we managed a patient with a ruptured large pararectal aneurysm arising from the right internal iliac artery presenting with an exsanguinating rectal bleed.